FTR allocations to ease transition to nodal pricing: An application to the German power system - Friedrich Kunz; Karsten Neuhoff; Juan Rosellón (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
A shift from zonal pricing to smaller zones and nodal pricing improves efficiency and security of system operation. Resulting price changes do however also shift profits and surplus between and across generation and load. As individual actorscan lose, they might oppose any reform. We explore how free allocation of financial transmission rights to generation and load can be used to mitigate the distributional impact. In a three node network we explore the fundamental effects with regard to reference node/hub for FTRs, the share of FTRs to be allocated for free and the metric to determine the proportion of rights allocated to different generation and load. We test the results in a more realistic setting based on hourly modelling of the German power system at nodal representation.
Keywords: L52; L94; Q40; D47; 330; Electricity market; Financial transmission right; Congestion management; Market design; Germany